Difference of Smoothness Breast Milk In Postpartum Mother Who Perfoming Lactation Massage And Consuming Breastfeeding Supplement In Tafali Spa And Pratama Afiyah Clinik of the Pekanbaru City (JURNAL PROTEKSI KESEHATAN, 2022)
Many benefits are obtained from exclusive breastfeeding, but very few mothers who do exclusive breastfeeding. I in Pekanbaru City in 2018 was43,9% and still did not reach the national target of 80%. The smooth production of breast milk will greatly affect the success of breastfeeding. Effort to increase milk suplements. This research is a quantitave a study with the research design used is Quasi Experiment through the design of Two Group Posttest Only. The sample in this study were 20 postpartum mothers obtained from the purposive sampling method. The research instrument used was on observation sheet. The result of the bivariateanalysis using the MannWhitney U test with a confidence level of 95% (α=0,05) value p-value = 0,056 means there is no difference of smoothness breast milk un postpartum mothers who perfomed lactation message and consuming breastfeeding supplement. It is recommended that the head of Tafali Spa and the head of Pratama Afiyah Clinik be able to provide lactation massage services to the postpartum mothers to help the smoothness breast milk of mothers who provide exclusive breasfeeding to their babies.